Antibacterial Activity and Fractional Antibiofilm Black Mulberry Leaf (Morus Nigra. L) against Bacterial Staphylococcus Aureus ATCC 25923 - Niva, Oktiva Cheria Kairul; Rahmawati, Ismi; Indrayati, Ana (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the antibacterial activity of extracts and fractions against S. aureus bacteria, the most active fraction of black mulberry leaves has antibiofilm activity against S. aureus bacteria, the most active fraction is located in the cell membrane wall  of S. aureus bacteria. The leakage of K+ metal ions and Ca2+ was carried out using the AAS  method and the morphology  of S. aureus  bacterial colonies was observed using the SEM method. The test result of the concentration inhibition % of 12.5 mg/ml had the highest average percentage, which was 40.01. The average IC50 value of inhibition is 24.57. The biofilm degradation test had with an average of 34.98. EC50 value 48.98.